Effects of Electromagnetic Fields (EMF)Near High Voltage Transmission Line: a Case Study - Quamruzzaman, M; Haque, Munima; Ahmed, Farruk; Zaman, Md Shabab (Bangladesh Journal of Medical Physics, 2015)
Abstract not available Bangladesh Journal of Medical Physics Vol.7 No.1 2014 66-68